Integrating Development Proposals into Organizational Workflow: Identifying Challenges, Barriers, and Opportunities in the Service Operations - Pöysä, Heidi (My University, 2025)
The aim of the study is to deepen the understanding of process innovation in low-hierarchy organizations, where ideas for improvement are generated through problems and suggestions for improvement identified in practice. The study will examine what innovation management practices can be applied to process development in such environments. The study is a case study of a team in an internationally operating technology industry organization, where working at the client interface provides a valuable insight into practical work and thus gives many ideas for improvement for the organization. A mixed-methods methodology was selected to gain an in-depth perception of the topic. Data were collected over a total period of four months. Qualitative data was collected through interviews and participant observations, while quantitative data was collected through a survey. The data obtained were combined and compared with each other to identify the challenges, barriers, and opportunities of the organizational development proposal process. The findings show that an open organizational culture and participative management contribute to the creation and progress of development proposals. Also, unclear structures and a lack of internal communication were found to be key barriers to progress on development proposals. The study showed that Lean thinking and continuous improvement principles can foster the systematic management of innovations arising from operational work. In particular, the results point to the importance of participative management and effective communication for the successful implementation of process innovations. Theoretically, this study adds to the literature on process innovation management, especially from the perspective of practice-based innovation in low hierarchical organizations. On a practical level, it provides applicable recommendations for organizations seeking to develop structures and models for the consistent use of innovation initiatives. The study is limited to the activities of the Finnish unit of Case Company, which leads to a strong contextualization of the results. As such, the results of the study cannot be generalized broadly to different organizations or sectors. A further study is recommended to investigate the impact of horizontal and vertical orientations on the innovation performance of companies. Additional case studies are also needed to contrast the specificities of process innovation in different industries.
Keywords: innovations; development (active); processes; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management